The emotional entanglements of smartphones in the field: On emotional discomfort, power relations, and research ethics. Issue 1 (18th March 2019) - Truong, Jasmine; Labhart, Florian; Santani, Darshan; Gatica‐Perez, Daniel; Kuntsche, Emmanuel; Landolt, Sara
Abstract : Despite human geographers' growing recognition of the need to explore how digital technologies are increasingly co‐producing geographies, the methodological implications of such forms of data production are rarely discussed. This paper explores how smartphones co‐constitute fieldwork when they are used as research instruments. Drawing from a research project on young people's nightlife in Switzerland, we use Ahmed's ideas of emotions to show how smartphones are not inert research tools but emotionally entangled in the field. We argue that doing research with smartphones visibly in fieldwork has an effect on the relationships between the people, practices, and places of the field site. More specifically, we propose that these effects of emotions call for a renewed scrutiny of research ethics, particularly as smartphones increasingly become part of research designs. Abstract : This paper explores how smartphones co‐constitute fieldwork when they are used as research instruments. We use Ahmed's ideas of emotions to show how smartphones are emotionally entangled in the field and argue that doing research with smartphones visibly in fieldwork has an effect on the relationships between the people, practices, and places of the field site. More specifically, we propose that these effects of emotions call for a renewed scrutiny of research ethics.